A novel injectable thermoresponsive and cytocompatible gel of poly(N-isopropylacrylamide) with layered double hydroxides facilitates siRNA delivery into chondrocytes in 3D culture. (1st September 2015) - Yang, Hsiao-yin; van Ee, Renz J.; Timmer, Klaas; Craenmehr, Eric G.M.; Huang, Julie H.; Öner, F. Cumhur; Dhert, Wouter J.A.; Kragten, Angela H.M.; Willems, Nicole; Grinwis, Guy C.M.; Tryfonidou, Marianna A.; Papen-Botterhuis, Nicole E.; et al.
Graphical abstract: Abstract: Hybrid hydrogels composed of poly( N -isopropylacrylamide) (pNIPAAM) and layered double hydroxides (LDHs) are presented in this study as novel injectable and thermoresponsive materials for siRNA delivery, which could specifically target several negative regulators of tissue homeostasis in cartilaginous tissues. Effectiveness of siRNA transfection using pNIPAAM formulated with either MgAl–LDH or MgFe–LDH platelets was investigated using osteoarthritic chondrocytes. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as an endogenous model gene to evaluate the extent of silencing. No significant adverse effects of pNIPAAM/LDH hydrogels on cell viability were noticed. Cellular uptake of fluorescently labeled siRNA was greatly enhanced (>75%) in pNIPAAM/LDH hydrogel constructs compared to alginate, hyaluronan and fibrin gels, and was absent in pNIPAAM hydrogel without LDH platelets. When using siRNA against GAPDH, 82–98% reduction of gene expression was found in both types of pNIPAAM/LDH hydrogel constructs after 6 days of culturing. In the pNIPAAM/MgAl–LDH hybrid hydrogel, 80–95% of GAPDH enzyme activity was reduced in parallel with gene. Our findings show that the combination of a cytocompatible hydrogel and therapeutic RNA oligonucleotides is feasible. Thus it might hold promise in treating degeneration of cartilaginous tissues by providing supporting scaffolds for cells and interference with locally produced degenerative factors.